Professores da UFT no ensino remoto: caracterização da sociedade de risco e análise do espaço-tempo pela teoria ator-rede - Silva, Maria Emília da (2025)
Contemporary society has witnessed the evolution of digital technologies in a wide range of sectors. In the field of education new ways of teaching and learning using these tools are also being experienced or discussed. In the years 2020/2021, we experienced a pandemic caused by the Sars-CoV-2 virus and, to face this situation, in schools and universities there was emergency remote teaching. In this thesis, the sociotechnical network that configured emergency remote teaching in higher education at the Federal University of Tocantins (UFT) at the Arraias/TO campus during the aforementioned period was investigated.This is a qualitative research, with field research, through interviews with thirteen professors from the five in-person undergraduate courses at this university. The main objective was to characterize emergency remote teaching as part of the risk society as defined by Ulrich Beck. We also used Bruno Latour's Actor-Network Theory (ANT) to understand the space and time that were performed in this sociotechnical network, highlighting deviations, compositions, and networks. The expression globalization-minus, defined by Latour (2020) to identify situations in times of crisis, will also be used. The main results were: TAR provided us with another bias in the perception of the sociotechnical network that involved space and time in emergency remote teaching, in which it deepened the understanding of the sociotechnical networks involved, examining how space, time, actors and practices were incessantly formed and negotiated. It was found that a situation of immediacy was performed on the part of students when it came to obtaining feedback from teachers; the issue of delays in synchronous meetings was perceived differently from in-person teaching. The connections between remote teaching and science, technology, politics, society, health and education became more visible. Regarding the risk society, it was evident that this period was very complex, bringing to light anguish, stress, insecurities, anxieties and a lot of uncertainty, by the interviewees in this unprecedented situation, due to the speed of decision-making in an uncertain scenario. The sketches of the networks also show the unprecedented scenario that was performed in this teaching.